NFM-15. BUILDING A NEUROFIBROMATOSIS THERAPEUTICS PROGRAM - Hemenway, Molly (Neuro Oncol, 2018)
Neurofibromatosis (NF) therapeutics is an emerging and growing field as more and more children are diagnosed with neurofibromatosis due to better awareness of the disease and diagnostic criteria. Patients with NF have an increased incidence of central nervous system (CNS) tumors and plexiform neurofibromas. Recent developments in the treatment of plexiform neurofibromas have significantly increased the numbers of patients seen for therapy. In order to provide high-quality care to these patients, a Neurofibromatosis Therapeutics Program (NFTP) should be developed and utilized. The program at Children’s Hospital Colorado has grown over the past few years and now includes a physician, nurse practitioner, nurse, and social worker. We collaborate closely with other disciplines that are vital in the care of the NF patient with plexiform neurofibromas and/or CNS tumors including: neuro-oncology, neurosurgery, neuroradiology, otolaryngology, orthopedics, plastic surgery, ophthalmology, neurology, dental, urology, dermatology, genetics, neuropsychology, and rehabilitation. Key players are identified in each subspecialty and then the NFTP is publicized to both primary care and subspecialty programs in order to identify patients who would be best cared for in this setting. Along with collaborating disciplines, the NFTP has developed protocols and standards of care for treatment, research, adverse reaction management, and data gathering to obtain prior authorizations for medications. The NFTP is actively conducting epigenetic research on plexiform neurofibroma tissue obtained during surgery. The NFTP is a strong and vibrant area of growth with the aim to provide high quality of care for the whole child and conduct lab and clinical research.